Traditional Indian Foods-Some Recent Developments - Arya, S. S. (Defence Science Journal, 2014)
Considerable progress has been made in the preservation of traditional Indian foods in ready-to-eat form and products like chapaties, stuffed parothas, halwa, upma, kheer, idli, avial, pullav, precooked dehydrated dhals, precooked dehydrated instantised pullav and alu-chholay have been preserved for periods ranging from 6 months to one year under ambient conditions either by thermal processing in cans and flexible retortable pouches or by the use of preservatives and dehydration. Processes have also been developed for freeze drying of tropical Indian fruits like mango and pineapple in the form of fruit juice powders. Preserved products have been utilized extensively during mountaineering expeditions, Antarctica expeditions and feeding of cosmonauts in space programmes. Some of the critical parameters in the process development and their role in the sensory quality of preserved foods have been highlighted.